Dynamical behavior of step-like transition of La0.5Sr0.5Mn1−xTixO3 in a widened field sweep rate. Issue 8 (September 2015) - Shang, C.; Xia, Z.C.; Wei, M.; Chen, B.R.; Jin, Z.; Huang, J.W.; Shi, L.R.; Ouyang, Z.W.; Huang, S.
Abstract: The magnetization behavior of Ti 4+ doped perovskite manganites La0.5 Sr0.5 Mn1− x Ti x O3 ( x =0.15, 0.175 and 0.2) was investigated. Experimental results show that Ti 4+ dopant suppresses the antiferromagnetic charge ordering and leads to a step-like magnetization behavior below 3 K. The step-like transitions and the critical magnetic fields are strongly dependent on the Ti doping level, magnetic field sweep rate and temperature. Above 3 K, the step-like transitions transform to broad ones. In addition, under pulsed high magnetic fields with an ultrafast field sweep rate of ~10 3  T/s, the sharp step-like transitions observed in the static magnetization measurements become smooth metamagnetic transition at low temperatures. This feature is correlated with the collapse of the balance between the magnetic energy and elastic energy in the phase separation system within a martensitic-like scenario.